Biomass-synthetic fiber modified high toughness cementitious composite material and method of making

CN122940419APending Publication Date: 2026-10-20HEILONGJIANG CONSTR TECH DEV CENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611118515.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

目前关于双尺度人工纤维混杂改性水泥基材料的研究已有报道,但融合槟榔纤维构建三级尺度内外协同增韧体系、同步解决纤维团聚、界面粘结、强碱降解、高延性与低成本平衡问题的技术方案尚未发现

Benefits of technology

[0028]1、本发明构建改性PVA纤维、静电纺PAN纤维、槟榔纤维三级尺度混杂协同增韧体系,静电纺PAN纤维填充基体微细孔隙、抑制早期塑性微裂纹,改性PVA纤维依靠优化界面粘结承担宏观拉应力,实现稳定应变硬化,控制裂缝宽度低于0.1mm,槟榔纤维填充基体大孔隙,降低胶凝材料用量、消纳槟榔加工固废,实现固废资源化,三类纤维在裂缝扩展不同阶段形成梯度阻裂效应,同步提升材料拉伸韧性、抗弯强度、抗干缩与抗渗耐久性能;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

A biomass-synthetic fiber modified high-toughness cement-based composite material and its preparation method are disclosed, relating to the field of building material preparation technology. The cement-based cementitious matrix comprises, by weight, 1300 parts tap water, 2700 parts 400# silicate cement, 2800 parts Class III fly ash, 110 parts silica fume, 1100 parts quartz sand, and 17 parts lignin sulfonate water-reducing agent. The tertiary-scale hybrid reinforcing fibers include modified PVA fibers, electrospun PAN fibers, and areca nut fibers. Through a tertiary-scale fiber gradient synergistic crack-inhibiting mechanism, micropores, microcracks, and macroscopic penetrating cracks are simultaneously controlled, bridging cracks of different scales in stages. This simultaneously improves the material's early shrinkage resistance, mid-to-late-stage high ductility, and long-term durability, achieving the advantages of high toughness, low shrinkage, low cost, and solid waste resource utilization with low total fiber content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building material preparation technology, specifically to a biomass-synthetic fiber modified high-toughness cement-based composite material and its preparation method. Background Technology

[0002] In recent years, infrastructure construction in cold regions, such as buildings, road repairs, seismic reinforcement, and seepage prevention projects, has continued to advance. Various high-stress and crack-prone engineering scenarios have placed demands on cement-based materials for high toughness, multi-crack crack control, and high durability. Currently, there are many types of cement-based materials for construction. Ordinary concrete is the most widely used due to its advantages such as readily available raw materials, simple construction, and low cost. However, it generally suffers from defects such as poor tensile toughness, susceptibility to penetrating wide cracks, and large drying shrinkage deformation, making it difficult to meet the construction requirements of high-ductility engineering components.

[0003] Most existing high-toughness ECC materials use single polyvinyl alcohol (PVA) fibers for toughening and reinforcement. Relying solely on macroscopic fiber bridging to suppress macroscopic cracks fails to constrain early plastic shrinkage microcracks at the microscopic level, resulting in significant problems with early cracking and insufficient long-term impermeability and durability. With the upgrading of the cold-region construction industry, engineering projects are simultaneously demanding comprehensive performance requirements for cement-based materials, including microscopic crack control, macroscopic toughening, low drying shrinkage, and low cost. Based on the micromechanical theory of fiber-assisted crack resistance, it is necessary to construct a multi-scale hybrid fiber system and develop high-toughness cement-based composite materials that combine excellent ductility and long-term durability.

[0004] Unmodified PVA fibers exhibit defects such as hydrophilic aggregation and interfacial bonding imbalance, while electrospun polyacrylonitrile (PAN) fibers can only seal micron-level microcracks and cannot withstand macroscopic tensile stress. Neither can achieve stable strain hardening when used alone. Introducing areca nut fiber as a natural plant reinforcement phase can further optimize the matrix's internal filling structure and reduce overall material costs. However, without synergistic blending, areca nut fiber exhibits poor compatibility with synthetic fibers, and the highly alkaline environment of cement easily degrades natural fibers, significantly weakening the long-term toughening effect.

[0005] Currently, there is a wealth of literature on reinforcing cement-based materials with single synthetic fibers or single natural plant fibers. However, research on hybrid systems combining modified PVA and electrospun PAN (polyvinyl acetate) fibers is limited. Furthermore, no reports have been published on schemes that simultaneously introduce areca fiber to construct a three-tiered hybrid system of "nano-microfibers - macro-synthetic fibers - natural coarse fibers." Research reveals that conventional PVA fiber-reinforced ECC materials improve toughness solely by increasing the fiber content, resulting in high fiber consumption, high raw material costs, and poor fiber dispersion. Electrospun PAN fiber-reinforced ECC materials only optimize the early microporous structure and cannot improve the material's ultimate tensile strain, making it difficult to meet the ECC multi-crack index. In addition, existing natural fiber concrete technologies often incorporate lotus root fibers, straw, or other plant fibers individually, failing to form a multi-tiered synergistic crack-resistant system with modified synthetic fibers. This means that shortcomings such as alkali corrosion, interfacial debonding, and fiber delamination and agglomeration of natural fibers cannot be addressed simultaneously. Currently, no hybrid fiber cementitious material scheme has been found that simultaneously employs a three-level composite of amino-polysiloxane-nano silica emulsion-modified PVA fiber, electrospun PAN fiber, and areca fiber. The inventors' research has found that the synergistic effect of these three-level fibers can achieve multi-level toughening through micropore filling, microcrack bridging, and macrocrack inhibition. Simultaneously, areca fiber can fill large pores in the matrix, reduce the amount of cementitious material used, and realize the resource utilization of solid waste.

[0006] Cement matrix cracking occurs throughout the entire service life. Relying solely on single-scale fibers cannot simultaneously address both early-age shrinkage control and the need for high ductility in later stages. Therefore, it is necessary to blend modified PVA fibers, electrospun PAN fibers, and areca fibers to create a gradient synergistic crack-resistant effect at different stages of crack propagation. While research on dual-scale artificial fiber hybrid modified cement-based materials has been reported, a technical solution that integrates areca fibers to construct a three-dimensional internal and external synergistic toughening system, simultaneously addressing issues such as fiber agglomeration, interfacial adhesion, strong alkali degradation, and the balance between high ductility and low cost, has yet to be discovered.

[0007] In summary, addressing the challenges of cracking, shrinkage, and durability in high-toughness cement-based materials for cold-region engineering, and leveraging the differentiated crack-inhibiting mechanisms of modified PVA fiber, electrospun PAN fiber, and areca nut fiber at three scales, a high-toughness cement-based composite material was prepared by utilizing the gradient synergistic toughening properties of these three types of fibers in crack propagation sequence. This material holds significant engineering value and environmental implications for cold-region infrastructure construction, including road repair, seismic components, and seepage prevention projects. Summary of the Invention

[0008] To address the shortcomings of the prior art, this invention provides a biomass-synthetic fiber modified high-toughness cement-based composite material and its preparation method. This material utilizes a three-level fiber gradient synergistic crack-resistant mechanism to simultaneously regulate micropores, microcracks, and macroscopic through-cracks. It uses amino-polysiloxane-nano silica composite emulsion to modify PVA fibers, enhancing the interfacial bonding performance of the matrix. Combined with electrospun PAN fibers to fill the micropores of the matrix and areca fibers to fill the macroporous structure, it bridges cracks of different scales in stages, simultaneously improving the material's early shrinkage resistance, mid-to-late-stage high ductility, and long-term durability. This achieves the advantages of high toughness, low shrinkage, low cost, and solid waste resource utilization with a low total fiber content.

[0009] To achieve the above objectives, the present invention adopts the following technical solution:

[0010] A biomass-synthetic fiber modified high-toughness cement-based composite material is composed of a cement-based cementitious matrix and three-dimensional hybrid reinforcing fibers, wherein:

[0011] The cement-based cementitious matrix comprises the following components by weight: 1300 parts tap water, 2700 parts 400# silicate cement, 2800 parts Class III fly ash, 110 parts silica fume, 1100 parts quartz sand, and 17 parts lignin sulfonate water-reducing agent.

[0012] The total volumetric content of the three-dimensional hybrid reinforcing fibers accounts for 1.5% to 2.5% of the total volume of the composite material, including modified PVA fibers, electrospun PAN fibers, and areca nut fibers, with a corresponding volume ratio range of 25% to 70%: 10% to 40%: 10% to 35%.

[0013] The modified PVA fiber was prepared by padding with an amino-polysiloxane-nano silica composite emulsion.

[0014] Furthermore, the modified PVA fiber has a tensile strength ≥900MPa, an elastic modulus ≥30GPa, and a water contact angle of 100°~105°.

[0015] Furthermore, the effective components of the aminopolysiloxane-nano silica compound emulsion are as follows by mass percentage: 60%~70% aminopolysiloxane, 15%~20% nano silica with a particle size of 10nm, 1%~2% epoxy silane coupling agent, and 8%~12% palm wax lubricant.

[0016] Furthermore, the electrospun PAN fiber has an average diameter of 0.8~1.2μm and a single fiber length of 10~15μm; the areca fiber is a fiber with a length of 2~6mm obtained by crushing and sieving dried areca shells, which is soaked in 2% dilute alkali solution at room temperature for 24h to remove lignin impurities before use, and then washed and dried.

[0017] Furthermore, the total volumetric content of the three-dimensional hybrid reinforcing fiber is 2.0%, and the volume ratio of modified PVA fiber, electrospun PAN fiber and areca fiber is 3:1:1.

[0018] A method for preparing a biomass-synthetic fiber modified high-toughness cement-based composite material includes the following steps:

[0019] Step 1: PVA fiber modification pretreatment: Prepare a cleaning solution containing AEO-9 and sodium carbonate, clean the PVA fiber at 90℃, and after cleaning and drying, impregnate it with an amino polysiloxane-nano silica composite emulsion, and then bake it to complete the siloxane grafting. After washing and drying, the modified PVA fiber is obtained and sealed for later use.

[0020] Step 2, Premixing of matrix dry powder: Add 400# silicate cement, Grade III fly ash, silica fume and quartz sand into a forced mixing equipment and dry mix until uniform to obtain mixed dry powder;

[0021] Step 3: Preparation of cement-based base slurry: Add tap water and lignin sulfonate water-reducing agent to the mixed dry powder, and stir evenly to obtain a cement slurry with stable fluidity;

[0022] Step 4: Add the three types of fibers in stages: First, add electrospun PAN fibers to the cement slurry in batches and stir continuously. Then, add areca nut fibers in batches and stir continuously. Finally, add modified PVA fibers in batches and stir continuously to ensure that the three types of fibers are evenly dispersed in the cement slurry.

[0023] Step 5, Casting and Standard Curing: The cement slurry mixed with the three types of fibers is poured into the mold, vibrated to remove internal air bubbles, covered and sealed, left to stand at room temperature, then demolded and moved into a standard curing room for 28 days to obtain the cement-based composite material.

[0024] Furthermore, in step one, the cleaning solution contains 2 g / L of AEO-9 and 2 g / L of sodium carbonate, and the cleaning time is 30 min; the concentration of the amino-polysiloxane-nano silica composite emulsion is 10 g / L, the padding temperature is 20℃, the time is 10 min, and the fiber to emulsion bath ratio is 1:10; the baking temperature is 120℃, the time is 1 min; and after washing, it is dried at 50℃ for 3 h.

[0025] Furthermore, in step four, the electrospun PAN fiber is stirred for 2 minutes, the areca nut fiber is stirred for 2 minutes, and the modified PVA fiber is added in 3-4 batches with a stirring time of 3 minutes.

[0026] Furthermore, in step five, the vibration time is 30 seconds, the room temperature settling time is 24 hours, the temperature of the standard curing room is 20±2℃, and the relative humidity is ≥95%.

[0027] Compared with the prior art, the beneficial effects of the present invention are:

[0028] 1. This invention constructs a three-level scale hybrid synergistic toughening system of modified PVA fiber, electrospun PAN fiber, and areca fiber. Electrospun PAN fiber fills the micropores of the matrix and inhibits early plastic microcracks. Modified PVA fiber bears macroscopic tensile stress by optimizing interfacial bonding, achieving stable strain hardening and controlling the crack width to less than 0.1 mm. Areca fiber fills the large pores of the matrix, reducing the amount of cementitious materials used and disposing of areca processing solid waste, thus realizing the resource utilization of solid waste. The three types of fibers form a gradient crack-resistant effect at different stages of crack propagation, simultaneously improving the tensile toughness, flexural strength, shrinkage resistance, and impermeability durability of the material.

[0029] 2. This invention modifies PVA fibers using an amino-polysiloxane-nano silica composite emulsion, solving the defects of fiber hydrophilic aggregation and interfacial debinding. Combined with a graded feeding process, it ensures uniform dispersion of multiple types of fibers. Under the same total fiber content, the ultimate tensile elongation of the material is more than 3 times higher than that of the single-doped unmodified PVA system, and the drying shrinkage rate is reduced by 25%.

[0030] 3. This invention uses domestic raw materials and areca nut processing by-products, which greatly reduces the overall cost of fiber raw materials. It can be widely used in engineering scenarios such as road repair, bridge seepage prevention, seismic reinforcement, and cold-region ECC components, and has significant economic benefits, durability advantages and environmental value. Attached Figure Description

[0031] Figure 1 This is a diagram illustrating the flexural failure morphology of the cement-based composite material prepared according to the present invention;

[0032] Figure 2 This is a diagram illustrating the fiber distribution on the fracture surface of the cement-based composite material prepared according to the present invention;

[0033] Figure 3 This is a comparison diagram of the tensile stress-strain curves of the cement-based composite materials prepared in the examples. Detailed Implementation

[0034] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the invention, not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0035] This embodiment provides a biomass-synthetic fiber modified high-toughness cement-based composite material, which is composed of a cement-based cementitious matrix and three-dimensional hybrid reinforcing fibers, wherein:

[0036] The cement-based cementitious matrix comprises the following components by weight: 1300 parts tap water, 2700 parts 400# silicate cement, 2800 parts Class III fly ash, 110 parts silica fume, 1100 parts quartz sand, and 17 parts lignin sulfonate water-reducing agent.

[0037] The total volumetric content of the three-dimensional hybrid reinforcing fibers accounts for 1.5% to 2.5% of the total volume of the composite material. The fibers include modified PVA fiber, electrospun PAN fiber and areca nut fiber, with a corresponding volume ratio range of 25% to 70%: 10% to 40%: 10% to 35%.

[0038] All of the above raw materials are commercially available finished products, and the key performance indicators of each raw material are limited as follows:

[0039] Cementitious aggregate additives: 400# silicate cement with a 28-day compressive strength ≥42.5MPa; Class III fly ash with a water requirement ratio ≤105%; silica fume with a SiO2 content ≥98%; quartz sand with a fineness modulus of 1.4~1.6, preferably 1.5; lignosulfonate water-reducing agent with a water reduction rate ≥18%, used to adapt high fiber content slurries to improve fluidity.

[0040] Modified PVA fiber: The tensile strength of the original filament is ≥900MPa, and the elastic modulus is ≥30GPa. The fiber is modified by padding with an aminopolysiloxane-nano silica composite emulsion. The water contact angle of the modified fiber is 100°~105°. The effective component mass ratio of the aminopolysiloxane-nano silica composite emulsion is: 60%~70% aminopolysiloxane, 15%~20% nano silica with a particle size of 10nm, 1%~2% epoxy silane coupling agent, and 8%~12% palm wax lubricant. Preferably, it is 68% aminopolysiloxane, 20% nano silica with a particle size of 10nm, 2% epoxy silane coupling agent, and 10% palm wax lubricant. The weight gain of the modified fiber is 1.5%, and the water contact angle is 102°, which effectively improves hydrophobic dispersion and interfacial adhesion.

[0041] Electrospun PAN fibers: with an average diameter of 0.8~1.2μm, preferably 1.01μm, and a single fiber length of 10~15μm, are used to fill micron-level internal pores and suppress early plastic microcracks.

[0042] Areca nut fiber: The fiber with a length of 2-6mm is obtained by crushing and screening dried areca nut shells. Before use, it is soaked in 2% dilute alkali solution at room temperature for 24 hours to remove lignin impurities, and then washed and dried to reduce the fiber degradation rate in the strong alkaline environment of cement.

[0043] The optimal fiber ratio is as follows: the total volume fraction of the three-dimensional hybrid reinforcing fiber is 2.0%, and the volume ratio of modified PVA fiber, electrospun PAN fiber and areca fiber is 3:1:1.

[0044] Based on the above-mentioned biomass-synthetic fiber modified high-toughness cement-based composite material, a preparation method is provided, including the following steps:

[0045] Step 1: PVA fiber modification pretreatment: Prepare a cleaning solution containing 2 g / L AEO-9 and 2 g / L sodium carbonate. Clean the PVA fiber at 90℃ for 30 min to remove the surface release oil. After cleaning and drying, use a 10 g / L amino polysiloxane-nano silica composite emulsion to impregnate the fiber at 20℃ for 10 min, controlling the fiber to emulsion bath ratio to be 1:10. Then bake at 120℃ for 1 min to complete the siloxane grafting. Finally, wash twice with water at room temperature and dry at 50℃ for 3 h to obtain modified PVA fiber for sealed storage.

[0046] Step 2, Premixing the matrix dry powder: Add 400# silicate cement, Grade III fly ash, silica fume and quartz sand to a forced mixing equipment and dry mix for 2 minutes to make the powder uniformly mixed to obtain mixed dry powder;

[0047] Step 3: Preparation of cement-based base slurry: Add tap water and lignin sulfonate water-reducing agent to the mixed dry powder, stir evenly to obtain a cement slurry with stable fluidity;

[0048] Step 4: Add the three types of fibers in stages: First, add electrospun PAN fibers to the cement slurry in batches and stir continuously for 2 minutes. Then, add areca nut fibers in batches and stir continuously for 2 minutes. Finally, add modified PVA fibers in 3 to 4 batches and stir continuously for 3 minutes. This will ensure that the three types of fibers are evenly dispersed in the cement slurry and that there is no agglomeration or stratification.

[0049] Step 5, Casting and Standard Curing: The cement slurry mixed with three types of fibers is poured into the mold, vibrated for 30 seconds to remove internal air bubbles, then covered and sealed with a film. After standing at room temperature for 24 hours, it is demolded and moved into a standard curing room with a temperature of 20±2℃ and a relative humidity of ≥95% for 28 days. After the performance test meets the requirements, the desired cement-based composite material is obtained.

[0050] The cement-based composite material prepared by this process exhibits a three-level gradient crack-prevention mechanism as follows: nanoscale electrospun PAN fibers fill the micropores of the matrix, blocking the initiation of early-stage plastic microcracks; modified PVA fibers rely on optimized interfacial bonding to bear macroscopic tensile stress, achieving stable strain hardening and multi-microcrack propagation; and treated areca fiber fills the macropores of the matrix, reducing the amount of cementitious materials used and facilitating the disposal of agricultural solid waste. These three types of fibers form a gradient synergistic toughening network in the early, middle, and late stages of crack propagation, constructing a multi-level regulatory system of micropore filling, micro-crack bridging, and macroscopic crack ductility inhibition, simultaneously reducing drying shrinkage and improving tensile toughness and long-term impermeability durability.

[0051] The prepared cement-based composite material under bending failure mode combination Figure 1 As shown, the fiber bridging effect at the mid-span crack is significant, the material maintains its integrity, and there is no brittle fracture; the fiber distribution on the fracture surface of the prepared cement-based composite material is well-coordinated. Figure 2 As shown, the fibers are randomly and uniformly distributed, with obvious pull-out marks, and the interfacial bonding state matches the optimal toughening requirements.

[0052] Four sets of examples are set up below. The cementitious matrix uses a standard fixed ratio. Only the total content and volume ratio of the tertiary hybrid fiber are adjusted to verify the effect of different ratios on the material properties:

[0053] Example 1

[0054] The total volumetric content of the three-stage hybrid fibers was 1.5%, with a volume ratio of modified PVA fiber, electrospun PAN fiber, and areca nut fiber of 7:2:1. Samples were prepared according to the above process, and their properties were tested after 28 days of standard curing. The tensile stress-strain curves were combined with... Figure 3 As shown.

[0055] Example 2

[0056] The total volumetric content of the three-stage hybrid fibers was 1.8%, with a volume ratio of modified PVA fiber, electrospun PAN fiber, and areca nut fiber of 5:3:2. Samples were prepared according to the above process, and their properties were tested after 28 days of standard curing. The tensile stress-strain curves were combined with... Figure 3 As shown.

[0057] Example 3 (Optimal Implementation Ratio)

[0058] The total volumetric content of the grade III hybrid fibers was 2.0%, with a volume ratio of modified PVA fiber, electrospun PAN fiber, and areca nut fiber of 3:1:1. Samples were prepared according to the above process, and their properties were tested after 28 days of standard curing. The tensile stress-strain curves were combined with... Figure 3 As shown.

[0059] Example 4

[0060] The total volumetric content of the three-stage hybrid fibers was 2.5%, with a volume ratio of modified PVA fiber, electrospun PAN fiber, and areca nut fiber of 3:1:3. Samples were prepared according to the above process, and their properties were tested after 28 days of standard curing. The tensile stress-strain curves were combined with... Figure 3 As shown.

[0061] A full set of mechanical and drying shrinkage tests were conducted on the 28-day standard curing specimens of the above four sets of examples. The performance indicators are shown in Table 1.

[0062] Table 1 Mechanical and drying shrinkage performance indices of each example after 28 days

[0063]

[0064] The above test standards are as follows: cubic compressive strength is tested according to GB / T17671-2021; uniaxial tensile properties are tested according to JC / T2461-2018 "Test Method for Mechanical Properties of High-Ductility Fiber Reinforced Cement-Based Composite Materials"; drying shrinkage properties are tested according to JTG3420-2020 "Test Procedures for Cement and Cement Concrete in Highway Engineering".

[0065] Comparative Analysis of Example Data

[0066] Example 3 represents the optimal mix ratio of the present invention, with a total fiber volume content of 2.0% and three types of fibers compounded in a 3:1:1 ratio. The compressive strength reaches 71.8 MPa, the ultimate tensile strain reaches 4.8%, the drying shrinkage strain is only 840 με, and the maximum crack width under ultimate load is stably ≤0.04 mm, meeting the requirements of the E5 grade high ductility concrete specification.

[0067] Compared with Example 1 (low amount of areca fiber): Example 1 lacks the natural coarse fiber filling the macroporous structure, the matrix porosity is increased, the drying shrinkage is increased by 50%, and the ultimate tensile strain is reduced by 33%, which proves that an appropriate amount of areca coarse fiber can significantly optimize the pore structure and inhibit drying shrinkage deformation.

[0068] Compared with Example 4 (excessive blending of areca fiber): In Example 4, excessive natural fiber introduces a large number of weak fiber-matrix interfaces, which are prone to premature debonding under stress, and compressive strength and tensile ductility decrease simultaneously, proving that there is a reasonable upper limit for blending areca fiber.

[0069] In addition, a control group (ECC with the same total adsorption of 2.0% and no modified PVA fiber) was set up for comparison: the ultimate tensile strain of the control group was only 1.1% and the drying shrinkage strain was 1120με. The tensile elongation of the optimal example 3 was increased by 3.2 times, the drying shrinkage was reduced by 25.7%, and the slurry did not clump or separate, and the adaptability of construction spraying was greatly improved.

[0070] In summary, this invention achieves three core properties simultaneously—high compressive strength, high ductility, and low drying shrinkage—through a three-level scale gradient synergistic toughening system composed of modified PVA fiber III, electrospun PAN fiber III, and pretreated areca nut fiber, while maintaining a moderate total fiber content. Simultaneously, it utilizes areca nut processing waste shells, significantly reducing the use of expensive imported synthetic fibers and lowering the overall raw material cost by over 65%. This invention is suitable for engineering applications such as thin-layer road repair in cold regions, seismic-resistant building surfaces, and underground seepage-proof linings, combining advantages in mechanical properties, durability, and the environmental value of solid waste resource utilization.

[0071] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered illustrative and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of the equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.

[0072] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A biomass-synthetic fiber modified high-toughness cement-based composite material, characterized in that: It is composed of two parts: a cement-based cementitious matrix and a three-dimensional hybrid reinforcing fiber, wherein: The cement-based cementitious matrix comprises the following components by weight: 1300 parts tap water, 2700 parts 400# silicate cement, 2800 parts Class III fly ash, 110 parts silica fume, 1100 parts quartz sand, and 17 parts lignin sulfonate water-reducing agent. The total volumetric content of the three-dimensional hybrid reinforcing fibers accounts for 1.5% to 2.5% of the total volume of the composite material, including modified PVA fibers, electrospun PAN fibers, and areca nut fibers, with a corresponding volume ratio range of 25% to 70%: 10% to 40%: 10% to 35%. The modified PVA fiber was prepared by padding with an amino-polysiloxane-nano silica composite emulsion.

2. The biomass-synthetic fiber modified high-toughness cement-based composite material according to claim 1, characterized in that: The modified PVA fiber has a tensile strength ≥900MPa, an elastic modulus ≥30GPa, and a water contact angle of 100°~105°.

3. The biomass-synthetic fiber modified high-toughness cement-based composite material according to claim 1, characterized in that: The effective components of the aminopolysiloxane-nano silica compound emulsion, by mass percentage, are: 60%~70% aminopolysiloxane, 15%~20% nano silica with a particle size of 10nm, 1%~2% epoxy silane coupling agent, and 8%~12% palm wax lubricant.

4. The biomass-synthetic fiber modified high-toughness cement-based composite material according to claim 1, characterized in that: The electrospun PAN fiber has an average diameter of 0.8~1.2μm and a single fiber length of 10~15μm; the areca fiber is a fiber with a length of 2~6mm obtained by crushing and sieving dried areca shells. Before use, it is soaked in 2% dilute alkali solution at room temperature for 24h to remove lignin impurities, and then washed and dried before use.

5. The biomass-synthetic fiber modified high-toughness cement-based composite material according to claim 1, characterized in that: The total volumetric content of the three-dimensional hybrid reinforcing fiber is 2.0%, and the volume ratio of modified PVA fiber, electrospun PAN fiber and areca nut fiber is 3:1:

1.

6. A method for preparing a biomass-synthetic fiber modified high-toughness cement-based composite material, characterized in that: The preparation method of the biomass-synthetic fiber modified high-toughness cement-based composite material according to claim 1 includes the following steps: Step 1: PVA fiber modification pretreatment: Prepare a cleaning solution containing AEO-9 and sodium carbonate, clean the PVA fiber at 90℃, and after cleaning and drying, impregnate it with an amino polysiloxane-nano silica composite emulsion, and then bake it to complete the siloxane grafting. After washing and drying, the modified PVA fiber is obtained and sealed for later use. Step 2, Premixing of matrix dry powder: Add 400# silicate cement, Grade III fly ash, silica fume and quartz sand into a forced mixing equipment and dry mix until uniform to obtain mixed dry powder; Step 3: Preparation of cement-based base slurry: Add tap water and lignin sulfonate water-reducing agent to the mixed dry powder, and stir evenly to obtain a cement slurry with stable fluidity; Step 4: Add the three types of fibers in stages: First, add electrospun PAN fibers to the cement slurry in batches and stir continuously. Then, add areca nut fibers in batches and stir continuously. Finally, add modified PVA fibers in batches and stir continuously to ensure that the three types of fibers are evenly dispersed in the cement slurry. Step 5, Casting and Standard Curing: The cement slurry mixed with the three types of fibers is poured into the mold, vibrated to remove internal air bubbles, covered and sealed, left to stand at room temperature, then demolded and moved into a standard curing room for 28 days to obtain the cement-based composite material.

7. The method for preparing a biomass-synthetic fiber modified high-toughness cement-based composite material according to claim 6, characterized in that: In step one, the cleaning solution contains 2 g / L of AEO-9 and 2 g / L of sodium carbonate, and the cleaning time is 30 min; the concentration of the amino-polysiloxane-nano silica composite emulsion is 10 g / L, the padding temperature is 20℃, the time is 10 min, and the fiber to emulsion bath ratio is 1:10; the baking temperature is 120℃, the time is 1 min; and after washing, it is dried at 50℃ for 3 h.

8. The method for preparing a biomass-synthetic fiber modified high-toughness cement-based composite material according to claim 6, characterized in that: In step four, the electrospun PAN fiber is stirred for 2 minutes, the areca nut fiber is stirred for 2 minutes, and the modified PVA fiber is added in 3-4 batches with a stirring time of 3 minutes each.

9. The method for preparing a biomass-synthetic fiber modified high-toughness cement-based composite material according to claim 6, characterized in that: In step five, the vibration time is 30 seconds, the room temperature settling time is 24 hours, the temperature of the standard curing room is 20±2℃, and the relative humidity is ≥95%.